Fibulin-5 mutations link inherited neuropathies, age-related macular degeneration and hyperelastic skin - Auer-Grumbach, Michaela (2011)
To identify the disease-causing gene responsible for an autosomal dominantly inherited Charcot–Marie–Tooth neuropathy subtype in a family excluded for mutations in the common Charcot–Marie–Tooth genes, we used array-based sequence capture to simultaneously analyse the disease-linked protein coding exome at chromosome 14q32. A missense mutation in fibulin-5, encoding a widely expressed constituent of the extracellular matrix that has an essential role in elastic fibre assembly and has been shown to cause cutis laxa, was detected as the only novel non-synonymous sequence variant within the disease interval. Screening of 112 index probands with unclassified Charcot–Marie–Tooth neuropathies detected two further fibulin-5 missense mutations in two families with Charcot–Marie–Tooth disease and hyperextensible skin. Since fibulin-5 mutations have been described in patients with age-related macular degeneration, an additional 300 probands with exudative age-related macular degeneration were included in this study. Two further fibulin-5 missense mutations were identified in six patients. A mild to severe peripheral neuropathy was detected in the majority of patients with age-related macular degeneration carrying mutations in fibulin-5. This study identifies fibulin-5 as a gene involved in Charcot–Marie–Tooth neuropathies and reveals heterozygous fibulin-5 mutations in 2% of our patients with age-related macular degeneration. Furthermore, it adumbrates a new syndrome by linking concurrent pathologic alterations affecting peripheral nerves, eyes and skin to mutations in the fibulin-5 gene.